Mechanisms of allergen-specific immunotherapy and allergen tolerance - (:unkn) unknown (JAPANESE SOC ALLERGOLOGY, 2020)
Allergen-specific immunotherapy (AIT) is the mainstay treatment for the cure of allergic disorders, with depicted efficacy and safety by several trials and meta-analysis. AIT impressively contributes to the management of allergic rhinitis, asthma and venom allergies. Food allergy is a new arena for AIT with promising results, especially via novel administration routes. Cell subsets with regulatory capacities are induced during AIT. IL-10 and transforming growth factor (TGF)-beta are the main suppressor cytokines, in addition to surface molecules such as cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) and programmed cell death protein-1 (PD-1) within the micro milieu. Modified T- and B-cell responses and antibody isotypes, increased activity thresholds for eosinophils, basophils and mast cells and consequent limitation of inflammatory cascades altogether induce and maintain a state of sustained allergen-specific unresponsiveness. Established tolerance is reflected into the clinical perspectives as improvement of allergy symptoms together with reduced medication requirements and evolved disease severity. Long treatment durations, costs, reduced patient compliance and risk of severe, even life-threatening adverse reactions during treatment stand as major limiting factors for AIT. By development of purified non-allergenic, highly-immunogenic modified allergen extracts, and combinational usage of them with novel adjuvant molecules via new routes may shorten treatment durations and possibly reduce these drawbacks. AIT is the best model for custom-tailored therapy of allergic disorders. Better characterization of disease endotypes, definition of specific biomarkers for diagnosis and therapy follow-up, as well as precision medicine approaches may further contribute to success of AIT in management of allergic disorders. Copyright (C) 2020, Japanese Society of Allergology. Production and hosting by Elsevier B.V.
Keywords: Allergy; Allergen-specific immunotherapy; Immune regulation; Immune tolerance; Innate lymphoid cells; INNATE LYMPHOID-CELLS; HOUSE-DUST MITE; REGULATORY T-CELLS; DENDRITIC CELLS; EPICUTANEOUS IMMUNOTHERAPY; EAACI GUIDELINES; TGF-BETA; SUBLINGUAL IMMUNOTHERAPY; INTRALYMPHATIC IMMUNOTHERAPY; SUBCUTANEOUS IMMUNOTHERAPY